PRODUCT VARIETY MANAGEMENT: A PROPOSAL OF METRICS AND INDICATORS FOR THE COSMETIC INDUSTRY | GESTÃO DE VARIEDADES DE PRODUTOS: UMA PROPOSTA DE MÉTRICAS E INDICADORES PARA A INDÚSTRIA DE COSMÉTICA - Oliveira, Luiz Thyerre; Oliveira, Carmine; Barros, Diego; Reis, Augusto Cunha; Dias, Ana Claudia; Silveira, Haydee (Brazilian Journal of Management and Innovation (Revista Brasileira de Gestão e Inovação), 2019)
This paper aims to present the problems faced by companies in relation to Product Variety Management (PVM), make the management of the company's product variety studied less complex and more dynamic, balancing the marketing team's objectives with the constraints of the industry, proposing suggestions to assist in decision making and presenting metrics for PVM evaluation. The variety of products is a current theme and present in the day to day business. With the proliferation of diversified and customized products to meet the demands of different market segments, companies face difficulties to manage the increasing in their portfolio, where excessive quantity of products can cause confusion in customers and difficulties in the operation. On the other hand, the scarcity of diversified products can mean loss of market share and competitiveness. The study is developed from the observation of the production of a cosmetics company located at Pavuna, state of Rio de Janeiro. Based on the knowledge of each department dynamics and variables involved with the offered product mix, this study indicates ways to minimize the difficulties arising from PVM, presenting management tools to streamline and improve product-related decision making. DOI: 10.18226/23190639.v7n2.01 Luiz Thyerre Oliveira, Centro Federal de Educação Tecnológica Celso Suckow da Fonseca (CEFET/RJ). Brasil. E-mail: thyerre.oliveira@gmail.com Carmine Oliveira, Centro Federal de Educação Tecnológica Celso Suckow da Fonseca (CEFET/RJ). Brasil. E-mail: carminemontico@yahoo.com.br Diego Barros, Centro Federal de Educação Tecnológica Celso Suckow da Fonseca (CEFET/RJ). Brasil. E-mail: diegoseelinger@gmail.com Augusto Cunha Reis, Centro Federal de Educação Tecnológica Celso Suckow da Fonseca (CEFET/RJ). Brasil. E-mail: professor.augusto.reis@gmail.com Ana Claudia Dias*, Centro Federal de Educação Tecnológica Celso Suckow da Fonseca (CEFET/RJ). Brasil. E-mail: missdias@gmail.com Haydee Silveira, Centro Federal de Educação Tecnológica Celso Suckow da Fonseca (CEFET/RJ). Brasil. E-mail: haydeemcsb@gmail.com Submetido: Julho 2018 Aceito: Janeiro 2019 *Contato para Correspondência